Sustainability awareness profile on global warming: a survey of physics education students at Universitas Sultan Ageng Tirtayasa - Asep Saefullah; Riandi Riandi; Taufik Rahman; Ida Kaniawati; Ida Hamidah; Nanang Winarno; Tresna Galih Sukma Suryana; Diana Ayu Rostikawati (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2026)
Sustainability awareness is an understanding and concern for environmental, social, and economic issues that enable current needs to be met without sacrificing future generations. The aim of this study is to determine the profile of sustainability awareness of physics education students at Universitas Sultan Ageng Tirtayasa, especially on the theme of global warming. Sustainability awareness comprises three dimensions: knowledge, attitudes, and behavior. The sample in this study comprised 80 students, 64 females, and 16 males. The research instrument used in this study was a Likert-scale questionnaire with 1-4 options: disagree, agree, and strongly agree. The results showed that students' sustainability awareness was 3.09, in the high category, but their sustainability knowledge was still in the medium category. The results also showed that gender did not influence sustainability awareness. Students from the Tangerang district had greater sustainability awareness than those from other regions.